Patterns of HIV care prior to antenatal care, and the impact on later outcomes, among pregnant women living with HIV in Gugulethu, South Africa: A retrospective cohort - Leonard, Bryan (Department of Public Health and Family Medicine, 2024)
Introduction: Women living with HIV (WLHIV) entering antenatal care (ANC) are at high risk of disengagement from antiretroviral therapy (ART). Increasing numbers of women conceiving are already on ART, but little is known about their patterns of care before ANC. We described ART history patterns before ANC among WLHIV and the association with maternal outcomes. Methods: We used existing data from a prospective cohort that enrolled WLHIV attending ANC in Gugulethu, South Africa. Data were collected through interviews and abstraction of electronic medical records. Self-reported ART history was examined, and women were grouped into (1) Newly starting ART, (2) ART-experienced without any interruptions, (3) ARTexperienced with interruption. Log-binomial models were used to assess the association between ART history, viral suppression at delivery and engagement in care at 12 weeks postpartum. Results: Among 321 women (median age 32.3 years, IQR 28.1-35.9; 61.4% in their first pregnancy), 52% were ART-experienced with no interruption (median years on ART 6.1, IQR 3.3-10.1), 32.7% were ART-experienced with at least one interruption (median years on ART 6.9, IQR 4.4-9.4), and 15.3% were newly starting ART in pregnancy. Among the 105 ARTexperienced women with interruption, 94.3% reported only one interruption. After adjusting for age, women newly initiating ART (adjusted risk ratio (aRR): 1.78; 95% CI: 0.91-3.79) and ART-experienced women with interruption (aRR: 2.39; 95% CI 1.39-4.35) were more likely to have a viral load >50 copies/ml at delivery when compared to ART-experienced women without interruption. After adjusting for age and relationship status, ART-experienced women with interruption (aRR: 6.20; 95% CI: 2.05-18.77) and without interruption (aRR: 3.10; 95% CI 0.99-9.71) were more likely to be disengaged from care at 12 weeks postpartum when compared to women newly starting ART. Conclusion: Most women in this study were ART-experienced before pregnancy, and a third had treatment interruption history. Women with any interruption had increased risk of being unsuppressed at delivery and disengaged from care at 12 weeks postpartum. These findings highlight the need to explore mechanisms driving these associations and examine possible interventions to support continuous engagement in HIV care postpartum.